A simple method to demonstrate that ice formation creates stratification in salt meromictic lakes ... - Voronova, Anna; Krasnova, Elena; Voronov, Dmitry (EARSeL eProceedings, 2015)
One of the possible factors determining the vertical stratification of the water column in the coastal meromictic Arctic lakes is the ice formation. When seawater is freezing, the salt brine concentrates in the ice pores and is later released under the ice. The aim of this research was to verify the hypothesis that ice formation is an important mechanism explaining water stratification in salty meromictic lakes of the Arctic coast. Seawater samples were frozen at a temperature of -10 degree Celsius for 12-24 hours, and then slowly thawed at room temperature during 1-2 days. Freezing/thawing was performed in 1.5 l and 2 l plastic bottles. In all bottles with initial salinity of 30 psu, a diluted layer with salinities between 3 and 15 psu (average 7 psu) was formed at the surface. Close to the ice/water interface, the salinity varied between 6 and 14 psu. At the bottom a thin layer with a salinity of 40-50 psu was created. These vertical salinity differences were preserved after a period of 24 h. Additional ...